2012
DOI: 10.1108/00907321211203667
|View full text |Cite
|
Sign up to set email alerts
|

Which platform do our users prefer: website or mobile app?

Abstract: PurposeAfter being implemented for two years, HKBUtube (the official video streaming site developed by Hong Kong Baptist University Library) has become a popular source of videos for the university. This video site also begins to draw the attention of the community. When more libraries are starting to respond to the demand for mobile service, the HKBU Library decided not to remain aloof. Before committing itself to the provision of an additional platform, the Library carried out a proof of concept to investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
4

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 7 publications
1
10
0
4
Order By: Relevance
“…With the advent of Mobile technologies users in developed and developing countries are adopting smart-phones (Han Rebekah Wong, 2012; Smura et al , 2009; Tian et al , 2009). The term Smartphone can be defined as “a mobile phone offering some computer-like functionality, including Internet access” (Kim et al , 2014, p. 578).…”
Section: Introductionmentioning
confidence: 99%
“…With the advent of Mobile technologies users in developed and developing countries are adopting smart-phones (Han Rebekah Wong, 2012; Smura et al , 2009; Tian et al , 2009). The term Smartphone can be defined as “a mobile phone offering some computer-like functionality, including Internet access” (Kim et al , 2014, p. 578).…”
Section: Introductionmentioning
confidence: 99%
“…These findings are steady with Oghuma, Chang, Libaque-Saenz, Park, and Rho (2015); Pantano and Priporas (2016) who argue that mobile advertising characteristics significantly influence behavioral outcomes. Similarly, these findings are in favor of Han Rebekah Wong (2012) who revealed that positive attitude of consumers towards mobile marketing would lead to positive intentions towards accepting and reading that mobile adverts.…”
Section: Credibility and Adoption Behaviormentioning
confidence: 81%
“…Dengan menggunakan sistem penjualan online atau disebut dengan ecommerce, proses penjualan dan promosi dapat dilakukan dengan lebih efisien karena semua orang dapat mengakses informasi mengenai kerajinan dengan mudah melalui gadget mereka masingmasing, informasi mengenai kerajinan yang diberikan pun [1]- [3] dapat dipastikan sangat informatif dan akurat karena proses pencatatan histori mengenai stok kerajinan dan histori pembelian pun dicatat dengan baik. Aplikasi e-commerce yang direkayasa pun berbasis mobile:apps android dikarenakan platform android sendiri sedang mengalami pertumbuhan pengguna, terlebih diwilayah Nusa Tenggara Timur [4], dan juga sistem berbasis mobile:apps sendiri memiliki beberapa keunggulan dibandingkan sistem berbasis mobile:web dari segi kecepatan, keamanan, dan juga lebih praktis dalam pengoperasiaanya [5], [6].…”
Section: Pendahuluanunclassified